The 2022 Qatar World Cup – An investigation into the media coverage of modern slavery and its effects on explicit attitudes towards and self-reported future engagement with Mega-Sporting Events. - Broad, Thomas (2022)
This research paper utilises the Qatar 2022 World Cup as a case study to investigate the prevalence of MS in supply chains, the perceptions of consumers on MS, and how these perceptions affect their consumer choices. The sample groups chosen varied in their country of occupation, with one group residing in the U.K., whilst the other were expatriates living in Qatar. Both groups were selected as young males aged 18 – 34. The results showed that participants were morally against modern slavery yet this did not entirely effect their consumer behaviour. To justify their ethical inaction, participants resorted to neutralisation technique and methods of legitimation to diminish internalised guilt. This paper concludes by outlining how the tendency to lean on these methods can further propagate the use of modern slavery in supply chains and provides recommendations for future researchers to tackle the phenomenon of modern slavery